Nilai-Nilai Ekonomi Islam Dalam Pelaksanaan Bagi Hasil Pengelolaan Kebun Karet Antara Etnis Madura Dengan Etnis Dayak Di Kubu Raya Kalimantan Barat - Rasiam Rasiam (Institut Agama Islam Negeri Madura, 2018)
The background of study has been about the interesting phenomena of cross-ethnical and cross-religious economic corporation practice among member of society. It unconsciously contains sharia values. This includes the practice of profit sharing of the rubber plantation management that has become the tradition of Kuala Mandor A villagers, the District of Kubu Raya, and it is hereditary generation practice. In terms of Fiqh literation, this practice is categorized as Musāqāh (plantation maintenance) that becomes the agreement between the plantation owner and the cultivator. The profit is shared based on the agreed portion which is called nisbah. The novelty of the study is that the profit sharing is agreed among people of cross-ethnical and cross-religions. According to the source, this agreement involves among Dayak-Madurese ethnics, Islamic-Christian religions, and among other believers. This practice lasts until present time. The problems of study are—firstly how is the practice of cooperation agreement of rubber plantation based on profit sharing in the village of Kuala Mandor A, secondly, how is the Islamic law view on the practice of profit sharing of rubber plantation between Dayak and Madurese ethnics in the village of Kuala Mandor A. This is a field research in design and employs descriptive-qualitative method. The research setting is in Kuala Mandor A village, the sub-district of Kuala Mandor B, the district of Kubu Raya.